Phenology and degree days of rice cultivars under organic culture - Islam, MR; Sikder, S (Bangladesh Journal of Botany, 2012)
Variations in the phenology and degree days of five fine rice cultivars viz., Rajshahi swarna, Silkumul, Kataribhog, Lal pajam and Sanla under organic and inorganic cultural conditions were studied following a split plot design. The requirement of days to attain various phenological stages was highest in Rajshahi swarna, medium in Silkumul, Kataribhog and Lal pajam and the lowest in Sanla for both the cultural conditions. The growing degree days (GDD) and heat use efficiency (HUE) were slightly higher under inorganic than organic culture because of higher life span of rice cultivars in inorganic culture. The highest GDD and HUE were found in Rajshahi swarna, whereas the lowest in Sanla. Results also showed that the requirement of days and GDD were initially higher up to maximum tillering stage under organic culture but thereafter these requirements were greater under inorganic culture for all the cultivars. The grain yield was somewhat lower in organic compared to inorganic culture. In Rajshahi highest grain yield of swarna was 2.90 and 2.74 t/ha under inorganic and organic culture, respectively. Key words: Phenology; Growing degree days; Heat use efficiency; Fine rice DOI: http://dx.doi.org/10.3329/bjb.v40i2.9770 Bangladesh J. Bot. 40(2): 149-153, 2011 (December)